Incorporation of Ions into Giant Molybdenum-oxide Cluster as a General Phenomenon - Omarali, Al-Ameen Bariz (Al-Nahrain Journal of Science, 2018)
In spite of the integration and concomitant release of all 16 Mo1 (necessary for ions Recently, the integration of different kinds of matter into giant wheel-shaped molybdenum-oxide clusters has been investigated with so-called chemical adaptability phenomenon. This refers to the integration of a large number of appropriate cations and anions even of the large “salt like” {M(SO4)}16 rings (M = K+ or NH4+) based on the cooperative/synergetic activation of silent receptor sites. An even more remarkable consequence of the flexibility behavior of the molecular giant wheel-shaped molybdenum-oxides of the type Mo176 and Mo154: the possibility of the integration of Cu2+ as tetrahedrally coordinated divalent cations at the same wheel area. In this study and in order to make the phenomenon as a general, the incorporation of ions into giant molybdenum-oxide cluster was expanded to involve the integration of some other cations (Fe2+, Co2+, Ni2+ or Zn2+) or salt like ring{Tl(SO4)}16. Uptake and almost half of the 16 Mo2 units the parent ring structure is maintained in the following resulting hybrids {(Mo146) (K(SO4))16} 1compound, {(Mo146) (NH4(SO4))16} 2 compound and {(Mo146) (Tl(SO4))16} 3. Moreover, the integrating of a tetrahedrally coordinated divalent cation like Fe2+, Co2+, Ni2+ or Zn2+ in addition to Cu2+, at the same wheel area (after releasing six Mo2-type building blocks of the parent wheel-shaped cluster) produced hybrid compounds with the general formula: [H4MIIn MoV28MoVI114O432(H2O)58]-26+2(n-5) (where MII= Fe2+, Co2+, Ni2+ or Cu2+, n=5, but with Zn2+, n=6) compounds (4–8). The result corresponds to the extreme flexibility of molybdenum-oxide building block linking resulting in the formation of a huge variety of structures from “molybdate” containing solutions (a unique molybdenum-oxide diversity phenomenon). The prepared compounds were characterized by CHN, Cit.Tit for the determination of the number of the MoV centers, spectroscopic methods (IR and UV-Vis) and X-ray crystallography (determination of the characteristic unit cell dimensions).